Options for Covid-19 Vaccines in Bulgaria – Acceptance and Hesitance - Petrova-Valkova D.; Serbezova A.; Yanakieva A. (Acta Medica Bulgarica, 2022)
The COVID-19 pandemic continues to take thousands of lives every day. Vaccine prophylaxis has been shown to be highly effective in both controlling and eradicating a number of communicable diseases, in particular COVID-19, as well as in preventing hospitalization and death. Globally, the level of vaccination varies widely. The aim of the present study was to study the attitude to vaccination against COVID-19 among the adult population in the Republic of Bulgaria. An online-based survey was performed to gather information on the attitudes of the population regarding the use of COVID-19 vaccines and the reasons for refusal. The survey includes 662 respondents from all over Bulgaria and covers the period from October 12, 2021 to October 22, 2021.